Neuropharmacological interactions in the rat pineal gland a study of antidepressant drugs - Banoo, Shabir (Rhodes University, Faculty of Pharmacy, Pharmacy, 1992)
The rat pineal gland provides a convenient model for investigating nor adrenergic receptor neurotransmission and the effects of various drugs on these processes in health and disease. The effect of a variety of antidepressant drugs on rat pineal gland function following acute and chronic administration is described. Antidepressants from several different classes increase melatonin synthesis in rat pineal gland cultures when administered acutely. This effect appears to be mediated by noradrenaline acting on postsynaptic Î²-adrenoceptors. Activation of these receptors, in turn, activates the enzyme serotonin N-acetyltransferase via a cyclic adenosine monophosphate (cAMP) second messenger system. Serotonin N-acetyltransferase catalyses the rate-limiting conversion of serotonin to melatonin. Blockade of postsynaptic Î²-adrenoceptors prevents the antidepressant-induced increase in melatonin synthesis. The possibility that atypical antidepressants as well as those that selectively inhibit serotonin reuptake may increase melatonin synthesis via a Î²-adrenoceptor mechanism is discussed. In contrast, however, antidepressants from different classes have variable effects on rat pineal gland function when administered repeatedly. Chronic treatment with antidepressants that selectively inhibit noradrenaline reuptake appear to down-regulate the Î²-adrenoceptor system while, simultaneously, increasing melatonin output. Atypical antidepressants and those that selectively inhibit serotonin reuptake appear to be without these effects when administered repeatedly. The pineal gland of normal rats may therefore not represent a suitable model for evaluating the biochemical effects of chronic antidepressant treatment. In an attempt to investigatc pineal gland function in rats with "model depression" , antidepressants were administered to chronically reserpinized rats. Treatment with reserpine produced an increase in the density of pineal Î²-adrenoceptors. In addition, pineal cyclic AMP accumulation and N-acetyltransferase activity were increased in reserpinized rats following exogenous catecholamine stimulation. Reserpine, by depleting intraneuronal catecholamine stores, prevented the nocturnal induction of N-acetyltransferase activity and reduced the synthesis of melatonin in pineal gland cultures. A variety of antidepressants, irrespective of their acute pharmacological actions, reversed these effects when administered chronically to resepinized rats. Acute antidepressant administration was not associated with a reversal of the reserpine-induced effects. These findings provide additional evidence against the hypothesis that antidepressant drugs act by reducing noradrenergic neurotransmission and casts doubt on the importance of Î²-adrenoceptor down-regulation in the mechanism of antidepressant action. The possibility that the pineal gland of the reserpinized rat may represent an alternative model for evaluating antidepressant therapies is discussed.
Keywords: Antidepressants -- Research; Pineal gland -- Research